Intelligent Systems in Production Engineering and Maintenance - ISPEM 2017 Proceedings of the First International Conference on Intelligent Systems in Production Engineering and Maintenance ISPEM 2017 - Burduk, Anna; Mazurkiewicz, Dariusz (Advances in Intelligent Systems and Computing,, 2018)
The volume presents a collection of 44 peer-reviewed articles from the First International Conference on Intelligent Systems in Production Engineering and Maintenance (ISPEM 2017). ISPEM 2017 was organized by the Faculty of Mechanical Engineering, Wrocław University of Science and Technology and was held in Wrocław (Poland) on 28-29 September 2017. The main topics of the conference included the possibility of using widely understood intelligent methods in production engineering. New solutions for innovative plants, research results and case studies taking into account advances in production and maintenance from the point of view of Industry 4.0 were presented and discussed-with special attention paid to applications of intelligent systems, methods and tools in production engineering, maintenance, logistics, quality management, information systems, and product development. The volume is divided into two parts: 1.          Intelligent Systems in Production Engineering 2.          Intelligent Systems in Maintenance This book is an excellent reference resource for scientists in the field of manufacturing engineering and for top managers in production enterprises.